Tunnels built in their own approaches. (February 2022) - Shaw, Andrew
Highlights: Construction of precast immersed tunnel elements within alignment. Alternative method of construction to traditional casting basin. Integration of temporary and permanent works. Design and construction of temporary works in weak Alluvium. Measures to ensure watertight seal around tunnel structure. Abstract: The Limerick Tunnel was constructed using the immersed tunnel technique in an 'in-line' casting basin or dry-dock within the footprint of the northern approach structures. The paper describes the benefits of this method of construction, the temporary works required to form the elements under challenging environmental conditions, namely poor ground conditions and a tidal river subject to large water level variation and strong currents.